Examine the value of the Minangkabau Proverb Manggantang Asok Maukia Langik and The Implications for Client Problems - Randi Saputra; Zubaidah Zubaidah (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
Minangkabau has many cultural values that can be used as a source of life, especially social life. Manggantang asok maukia langiak is a form of expression of proverb valuesthat is used as a way of life for the Minangkabau community. Examining the value of this proverb is one of the aims of researchers to examine the value contained and its implications in counseling. This research is limited to the value of the adage of manggantang asok maukia langik as a value that explains the nature of a problem. This research uses hermeneutic qualitative method. The results of this study explain that 1) the value contained in the saying Manggantang asok maukia langiak is something that is irrational, and 2) every problem has a cause. Manggantang asok maukia langiak is a value that is believed by the Minangkabau community as a form of behavior beyond ability, an impossible and futile act to do and an act that has never been done, so this is concluded as a form of irrational thinking. This view describes irrational thoughts about a behavior or action that causes problems.